Phenotypic and Genotypic Spectrum of Indian Patients with Hypophosphatasia - Melkunte S. Dhananjaya; S. Thrupti; Hamsa V. Reddy; Anusha Nadig; Kenchappa S. Adarsh; Swati Jadhav; Parvathy Lalitha; Sandhya Nair; Shaila Bhattacharyya; Anurag Lila; Vijaya Sarathi (Indian Journal of Endocrinology and Metabolism)
Introduction: Hypophosphatasia (HPP) is a rare disorder, with only two genetically proven cases reported from India. Here, We report five Indian patients with genetically proven hypophosphatasia and describe their clinical, biochemical, and genetic profiles. Methods: The study included patients with genetically proven hypophosphatasia managed at different healthcare centers in South India. The participants’ case records were reviewed, and relevant phenotypic and genotypic information was collected and analyzed. Results: Case 1 presented at 4 months of age for failure to thrive, found to have persistent hypercalcemia for which she received bisphosphonate therapy. A low alkaline phosphatase was recognized later. Case 2 presented during adolescence with bilateral genu valgus and delayed dentition with classical tongue-like translucencies on radiology and low alkaline phosphatase. Genetic evaluation in cases 1 and 2 revealed compound heterozygous variants in the ALPL gene. Case 1 received asfotase alfa with remarkable improvement in growth. Case 3 presented with multiple vertebral fractures at 33 years of age whereas cases 4 (42 years) and 5 (63 years) presented with musculoskeletal pains with delayed diagnosis for 8 and 13 years, respectively. Cases 3–5 had heterozygous variants in the ALPL gene. Conclusions: In the largest case series of hypophosphatasia from India, we report five cases of hypophosphatasia with two novel variants. Our study emphasizes the need to increase awareness regarding the disease to improve its early diagnosis and also, the need to form strategies to reduce the challenges in obtaining enzyme replacement therapy for hypophosphatasia in India.